Dzielnicowy w roli pedagoga = Community police officer as an educator - Stankiewicz, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the range of tasks and responsibilities that a community police officer - a street educator - has to fulfil in his/her daily service. The author synthesises the tasks facing the streetworker, which are aimed at adolescents and adults. Community education described in the paper is based on mutual trust and respect between the police representative and the citizen. The relationships established with the community and functioning in the local environment emerge as determinants for fulfilling the responsible role of the street educator. The information presented in the article was developed following a substantive analysis of texts and source studies.
Keywords: community police officer; educator; streetworking; dzielnicowy; pedagog